Sleep-disordered breathing and neurobehavioral symptoms in children in a Southeast Nigerian city - Ayuk, Adaeze Chikaodinaka; Uwaezuoke, Samuel Nkachukwu; Ndu, Ikenna Kingsley; Iloh, Kenechukwu Kosisochukwu; Bisi-Onyemaechi, Adaobi Ijeoma; Ndukwu, Chizalu Ifeyinwa; Ekwochi, Uchenna; Asinobi, Isaac Nwabueze; Nduagubam, Obinna Chukwuebuka; D I Osuorah, Chidiebere (Indian Journal of Child Health, 2019)
Introduction: Sleep-related breathing difficulties can lead to neurobehavioral symptoms in children. They can be assessed through validated screening questionnaires. Objective: This study aims to determine the prevalence of sleep-disordered breathing (SDB) among children, as well as neurobehavioral symptoms and associated risk factors. Materials and Methods: Descriptive cross-sectional study was conducted using the pediatric sleep questionnaire to assess sleep habits such as snoring and sleep apnea; neurobehavioral symptoms such as easy distractibility and disruptive behavior. The sample size of the study was 400 participants consecutively enrolled from consenting households in the enumeration areas in Enugu, Southeast Nigeria. Percentage prevalence of neurobehavioral symptoms was calculated, and SDB scores assigned with the determining cutoff score of >0.33. Analyses for an association of SDB score with socio-economic class (SEC), age, and gender, were performed using relevant statistics. Results: Of the 338 children aged between 2 and 18 years, 47% (158) were males. Children between 2 and 5 years represented 30% (101), while 59% (110) and 11% (46) were children 5–10 years and >10 years, respectively. The mean age of all participants was 6.4±3.1 years, 10% (34) belonged to SEC one while 49% (164) and 41% (139) belonged to middle and lower classes, respectively. At least one of SDB symptoms was present in 73% (248) of participants, but the SDB criteria score was met by 45 participants giving a prevalence of 13.3%. The most prevalent neurobehavioral symptoms were bed wetting in 56.8% (192), easy distractibility in 50.9% (167), and excessive day time sleepiness in 41.3% (139) cases. SDB was more likely in children with up to seven neurobehavioral symptoms, with an odds ratio of 8.27 (CI 3.48–19.66). Conclusions: SDB prevalence rate was found to be high in the present estimated pediatric population. The presence of seven or more neurobehavioral symptoms was associated with SDB and was predominant in children aged between 5 and 10 years.